Not all planar graphs are in PURE-4-DIR - Gonçalves, Daniel (Journal of Graph Algorithms and Applications, 2020)
We prove that some planar graphs are not intersection graphs of segments if only four slopes are allowed for the segments, and if parallel segments do not intersect. This refutes a conjecture of D. West [D. West, SIAM J. Discrete Math. Newsletter, 1991].